Examining Sex Offending and Victimization: Advancing Research on Prevalence, Impact, and Context - Gillespie, Lane K. (Victims & offenders, 2025)
This special issue focuses on sexual offending and victimization research, and this introduction provides an overview of the articles included herein. These wide-ranging studies highlight the breadth of current research and emerging areas of study. Several pieces in this issue make methodological contributions - validating scale measures, emphasizing overlooked populations, and utilizing novel sampling approaches and study designs - and explore less examined topics within sexual offending and victimization. Collectively, these studies contribute to burgeoning research in this area, providing context relating to identification, risk, consequences, and response.